2011
DOI: 10.1007/s11295-011-0377-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of monoterpene synthases from Litsea cubeba (Lour.) Persoon

Abstract: Mountain pepper (Litsea cubeba (Lour.) Persoon) is an evergreen tree in the Lauraceae family and has attracted attention for the antioxidant and antibacterial effects of its essential oils. The dominant components of the essential oil of L. cubeba are monoterpenes. To investigate the biosynthesis of monoterpenes that have bioactivity in L. cubeba, three cDNAs corresponding to monoterpene synthase genes were isolated, and the corresponding enzymes were functionally characterized in vitro. The genes obtained wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…The number of terpene synthases identified from L. cubeba , ten monoterpene synthases and four sesquiterpene synthases, and the three functionally characterized monoterpene synthase gene sequences have been deposited in the NCBI GenBank database and functionally characterized [11]. At present, a relatively large number of TPSs have been found in plants with genomic sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of terpene synthases identified from L. cubeba , ten monoterpene synthases and four sesquiterpene synthases, and the three functionally characterized monoterpene synthase gene sequences have been deposited in the NCBI GenBank database and functionally characterized [11]. At present, a relatively large number of TPSs have been found in plants with genomic sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the medicinal and economic importance of L. cubeba , little genomic information is available for this non-model genus, and only 40 nucleotide sequences have been deposited in the NCBI GenBank database (as of the 22 nd of May 2013). To date, three genes involved in monoterpene synthases have been functionally characterized [11], showing the potential for genomic research on this plant. However, a lack of sequence data has limited extensive and intensive research.…”
Section: Introductionmentioning
confidence: 99%
“…3), in which the majority of angiospermous monoterpene synthases reside (Chen et al, 2011). The TPS sequences most similar to LnTPS1 are those of a-thujene synthase from L. cubeba (Lauraceae; Chang and Chu, 2011), with 92% identity, and a-terpineol synthase from M. grandiflora (Lee and Chappell, 2008), with 57% identity.…”
Section: Analysis Of Sequences Of Terpene Synthases From L Nobilismentioning
confidence: 99%
“…Previous studies in the basal dicots have identified a few TPS genes encoding monoterpene synthases in Litsea cubeba (Lauraceae; Chang and Chu, 2011) and monoterpene and sesquiterpene synthases in Magnolia grandiflora (Lee and Chappell, 2008). These studies have shown that the monoterpene synthases fell into clade b, to which most monoterpenes from the eudicot species belong, suggesting that clade b diverged from the rest of the TPS gene family at the base of the angiosperms.…”
mentioning
confidence: 94%
“…Functional characterization of EtLIM: The activity of EtLIM was measured in vitro GC/MS analysis as described by Chang and Chu (2011) with slight modifications. The purified protein (20 μg) was added to monoterpene synthase buffer [25 mM HEPES (pH 7.2), 100 mM KCl, 10 mM MgCl 2 , 10% (v/v) glycerol, 5 mM DTT] with 30 μM GPP (Sigma).…”
Section: Methodsmentioning
confidence: 99%